Ventilation pathways and epitympanic retraction in chronic non-cholestheatomatous otitis media - Gonzales Diaz, Víctor Hugo (2022)
Objective: To describe the endoscopic findings of the ventilation pathways found during type I tympanoplasty in patients with non-cholesteatomatous COM (chronic otitis media). Materials and methods: Cross-sectional descriptive study, we evaluated 32 patients with non-cholesteatomatous COM with and without epitympanic retraction (ER) (Grade I-III, according to Mirko Tos classification), with a history of type I tympanoplasty (June, 2018 – January, 2020) in the otorhinolaryngology service of the Arzobispo Loayza National Hospital. Patients with previous middle ear surgeries, with cholesteatomatous COM, with ER grade IV and surgical acts not digitally stored were excluded. Results: 71.8% of patients presented ER (Grade I 3.0%, grade II 30.0% and grade III 56.5%), all presented blocked tympanic isthmus (TI). 68.8% of participants with ER presented complete tensor fold (TF). A significant relationship was observed between complete TF and blocked IT with ER (p=0.026 and 0.003, respectively). Conclusions: The most frequent findings were complete TF and blocked IT, these had a significant association with the presence of ER in patients with non-cholesteatomatous COM.